Prevalência e fatores associados a multimorbidade e idoso - Cavalcanti, Gustavo (2016)
The aging process is speeded to a worldwide level due to the increasing of life’s expectancy rates. As we age, the occurrence of chronic diseases become usual, as well as the multimorbidity, that is, the appearance of two or more chronic diseases in the same person. Multimorbidity may cause functional incapacities, loss in the quality of life, the use of health services and a higher death risk. The household may influence in these factors showing possible differences among elderly residents with multimorbidity in different environments. Therefore, the goal of this study is to evaluate the association between elderly’s multimorbidity and sociodemographic variables, health self-perception and polypharmacy. It is a piece of study performed by Dellani (2011) and Mascarello (2012). The data was collected in the period between 2010 and 2011 by household survey, using the Health Welness an aging (SABE)questionnaire, which was applied to elderly that lived in the towns of Coxilha and Estação. The data was analyzed through descriptive and inferential statistics. Multimorbidity was considered a dependent variable and as the independent variables, we have the sociodemographic ones related to life and health’s habits that are presented in the Health, Well -Being and Aging questionnaire. To evaluate the association between multimorbidity and independent variables, the bivariate analysis by the test χ2, with a level of significance of 5%, was used. Prevalence and confidence interval ratios of 95% in the robust and adjusted analysis were used, bothconducted by Poisson’s regression model. In the multiple model, the variables that had a p value inferior to 0.20 in the bivariate analysis were considered and were kept in the model with those in which p < 0.05. Multimorbidity was shown to be associated with negative health self perception and the use of polypharmacy, interfering in the elderly’s quality of life. The result of the study demonstrates the negative self-perception of health and the use of polypharmacy associated with multimorbity. The study could contribute to identify the needs of the elderly with multimorbity, as well as to deepen the political reflection in the region, improving the health planning considering the population characteristics in the different contexts.